Tree-Crop Interaction in Albizia procera Based Agroforestry System in Relation to Soil Moisture, Light and Nutrients - Newaj, Ram; Bhargava, M. K.; Yadav, R.S.; singh, Ajit; Shanker, A.K. (Indian Journal of Agroforestry, 2020)
A field experiment was conducted in a randomized block design at National Research Centre for Agroforestry, Jhansi (U.P.) during two consecutive years (2000-01 and 2001-02). The experiment comprising six treatments viz. T1- Trees allow to grow normally + crop, T2 - Pruning of trees up to 70 % plant height + crop, T3 - Trees allow to grow normally + soil barrier + crop, T4 - Pruning of trees up to 70 % plant height + soil barrier + crop, T5 - T1 + irrigation as per requirement of crop, T6 - Pruning of trees up to 70 % plant height + irrigation as treatment 5,T7- Pure trees and T8- pure crops (control). Blackgram (Phaseolus mungo Roxb.) - mustard (Brassica juncia Coss.) crop sequence was included as intercrop in tree-crop system. During first year, the growth performance of Albizia procera (height, collar diameter and crown diameter) was less with intercrops (blackgram and mustard) as compared to that pure trees, but after well establishment of trees, the growth of trees was improved with intercrops during second year compared to that of pure trees. Germination, plant height and branching of intercrops (blackgram and mustard) in first row from the tree base was less as compared to second, third and fourth rows from tree base during both the years. The higher values of these characters were observed in pruning of trees up to 70 per cent plant height irrespective of irrigation and soil barrier as compared to other treatments during both the years. Overall, the germination, plant height and branching in pure crops were higher as compared to tree-crop system. The competitive effect of trees on yield attributes and yield of blackgram and mustard was only observed in first row of crop from tree base during first year and this difference was widen during second year. Among all the treatments, pruning of trees up to 70 per cent plant height significantly had higher values of yield attributes and yield either with irrigation or soil barrier. In overall comparison, the grain yield of pure crop was higher as compared to that of tree-crop system. The light intercepted by under storey crops (blackgram and mustard) was more in pruning of trees up to 70 per cent plant height than trees allowed to grow normally. However the value of light intercepted by crops was less in tree-crop system than open field. The soil barrier was fully able to restrict the movement of root. But in case of other treatments (trees allowed to growing normally and pruning of trees up to 70 per cent plant height) the horizontal movement of roots after a year of planting was observed up to 1.0 m. Root length density was higher at 0.5m away from tree base as compared to 1.0, 2.0 and 3.0m away from tree base. Similarly, specific root length was less at 0.5 m away from tree base and it increased with increasing distances from tree base.